Implementation of Spice Route History Materials in Grade 11 History Instruction at SMA Negeri 6 Samarinda - Resty Apriliani; Siti Marfuah (Yupa: Historical Studies Journal, 2025)
The purpose of this study was to investigate how the history of the Spice Route was taught in grade XI at SMA Negeri 6 Samarinda. The main focus of this study was on how the materials were implemented and the challenges faced when using the spice route materials for teaching. To gain a comprehensive understanding of the learning process, this study combined descriptive methods with qualitative approaches. Direct observation, teacher and student interviews, and supporting documentation were some of the data collection methods. The findings of the study indicate that the use of spice route materials for teaching history at SMA Negeri 6 Samarinda is quite effective. Teachers' learning planning prepares Learning Outcomes (LO), Learning Objective References (LOR), and teaching modules. The stages of implementing teacher learning use lecture and discussion learning methods. The evaluation given by the teacher is an essay assignment, students are asked to relate ocean exploration to the spice route. The obstacles experienced are the lack of diverse learning methods, the lack of student activity, and the teacher is too fast in explaining the material.